Formulation, Development And Evaluation Of Metformin Hydrochloride Sustained Release Tablets - DRK.L.SENTHILKUMAR; R.P.EHIZILMUTHU (International Journal of Pharma and Bio Sciences, 2011)
There is a continuously growing interest in the pharmaceutical industry for extended release oral drug delivery systems. There is also high interest for design of dosage formulations that allow high drug loading, particularly for actives with high water solubility. The Study was undertaken with an aim to formulation development and evaluation of Metformin sustained release tablets using different polymers as release retarding agent. It is concluded that formulation of sustained release tablet of Metformin containing 13 % HPMC K100 with binder PVP K30 i.e. batch IX can be taken as an ideal or optimized formulation of sustained release tablets for 10 hour release as it fulfills all the requirements for sustained release tablet.